The reception of D.H. Lawrence in Europe - Jansohn, Christa (Athlone critical traditions series., 2007)
The intellectual scope and cultural impact of British and Irish writers cannot be assessed without reference to their 'European' fortunes. This collection of essays records the ways in which D.H. Lawrence's work has been received, translated and published in different area's of Europe.